EFFICIENCY OF COMPLEX RESEARCHES OF INTERMOUNTAIN BASINS UNDERGROUND WATERS EXPLOITATION: (on the pattern on the Ararat intermountain basin) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
Though to the present time fulfilled researches in the sphere of water resources, water supply situation in the Republic of Armenia remains unsatisfactory. In this connection the Ararat intermountain basin underground waters have a special interest. In the paper the issues of palaeohydrogeological zoning the relation between contemporary and ancient watersheds have been discussed. On the basis of mathematical modelling the influence of underground water concentrated collection in the foothill part of the territory on their regime in the plain part of the basin has been assessed.
Keywords: Ararat intermountain basin; palaeohydrogeological zoning; watersheds